Random perturbation of the variable metric method for unconstrained nonsmooth nonconvex optimization - El Mouatasim, Abdelkrim; Ellaia, Rachid; Souza de Cursi, José E. (Zielona Góra: Uniwersytet Zielonogórski)
We consider the global optimization of a nonsmooth (nondifferentiable) nonconvex real function. We introduce a variable metric descent method adapted to nonsmooth situations, which is modified by the incorporation of suitable random perturbations.
Keywords: nonconvex optimization; stochastic perturbation; variable metric method; nonsmooth optimization; generalized gradient